2017
DOI: 10.1136/bmjopen-2017-016294
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a new parallel primary healthcare centre and on-campus training programme on history taking, physical examination skills and medical students' preparedness: a prospective comparative study in Taiwan

Abstract: ObjectivesThe primary healthcarecentre (PHCC) is the first place that medical students experience patient contact. Usually, medical students are frustrated by a lack of proper skills training for on-campus history taking (HT), physical examination (PE) and self-directed learning (SDL) to prepare for their PHCC and inhospital patient contact. For pre-clerks, this study aims to compare the effectiveness of PHCC training and PHCC training in combination with on-campus HT and PE training modules (PHCC+on-campus) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
2
1
0
Order By: Relevance
“…While practical medical experience forms an integral part of medical curricula in Anglo-Saxon or Scandinavian countries [11,12,40,41], this is not the case for other countries [42,43]. Our research is in line with other studies which report positive effects of early practical medical experience not only in diverse medical abilities, but also in student's interest and motivation to further improve their practical skills throughout their time in medical school [44][45][46].…”
Section: Discussionsupporting
confidence: 85%
“…While practical medical experience forms an integral part of medical curricula in Anglo-Saxon or Scandinavian countries [11,12,40,41], this is not the case for other countries [42,43]. Our research is in line with other studies which report positive effects of early practical medical experience not only in diverse medical abilities, but also in student's interest and motivation to further improve their practical skills throughout their time in medical school [44][45][46].…”
Section: Discussionsupporting
confidence: 85%
“…12 Moreover, we also introduced the basic clinical skill course in the fourth year of the curriculum, and a previous comparative study showed that trainees' basic clinical skills training in medical schools outperformed those under the traditional curriculum. [40][41][42] In the present study, we found that school grades could be a reliable predictor of clinical performance. Our prediction model could accurately predict the clinical performance in the validation cohort in the same institution.…”
Section: Discussionsupporting
confidence: 56%
“…PHCC has clinical features of insidious onset, non-obvious early symptoms and rapid progression. Nevertheless, with the development of medical science, the technology of early diagnosis of PHCC has greatly improved, and more patients with PHCC can undergo radical treatment (24). However, studies have also reported that the cumulative incidence of recurrent hepatocellular carcinoma (RHCC) after PHCC is 70–88% (5), and the recurrence after PHCC is an important factor of survival prognosis (6).…”
Section: Introductionmentioning
confidence: 99%